Competing globally with cost accounting: a case study - Pedro, M. I.; Martins, J. C.; Filipe, J. (International Journal of Latest Trends in Finance and Economics Sciences, 2018)
In recent years, information has played a key role in business competitiveness, allowing not only to inform managers about external contexts, but also to internal problems. Thus, cost accounting has relevant tools, with the ability to provide information about how the resources of a company are used, making it possible to evaluate and improve their performance. The main goal of this research is to develop a different costing system model to a company, in order to provide distinct information on the costs of production processes, to help managers make better operational and strategic decisions. This company business is processing and packaging fruit and vegetables, in particular they are organized by three main sectors: fruit, potatoes and 4th range products. Those cost allocation methodologies could be identified, on one hand, the profitability of each product, helping to define the best medium-term strategy and, on the other hand, some operational faults. Basically, this work aims to prove the importance of costing models to improve the performance and the competitiveness in a real context.